Bavachin enhances paclitaxel sensitivity in ovarian cancer cells through modulation of mitochondrial function and ER stress - Sang-Jin Lee; Kee K. Kim; Jin-Young Lee (Animal Cells and Systems)
Bavachin, a bioactive phytoestrogen from Psoralea corylifolia, has shown promising therapeutic potential in various cancers, but its effects on ovarian cancer remain unexplored. In this study, we investigate the anti-cancer mechanisms of bavachin in ES2 and OV90 ovarian cancer cells and its potential to enhance paclitaxel sensitivity. Bavachin significantly inhibited cell proliferation and spheroid formation while inducing caspase-dependent apoptosis through modulation of Bcl-2 family proteins. Mechanistically, bavachin disrupted mitochondrial function by inducing membrane depolarization and calcium dysregulation, leading to comprehensive impairment of cellular bioenergetics including both oxidative phosphorylation and glycolysis. Furthermore, bavachin activated the endoplasmic reticulum stress pathway as evidenced by upregulation of GRP78, ATF4, PERK, and CHOP, and notably inhibited phosphorylation of ERK1/2 and p38 MAPK signaling pathways essential for tumor cells survival. Combination treatment with bavachin enhanced the cytotoxic effects of paclitaxel, showing synergistic anti-cancer activity in both cell lines. These findings demonstrate that bavachin effectively suppresses ovarian cancer growth through multiple mechanisms and may serve as a promising therapeutic agent, particularly in combination with conventional chemotherapy.